The solution-centric organization - Eades, Keith M. (McGraw-Hill, 2006)
The Solution-Centric Organization provides a comprehensive framework for moving companies away from a product/price orientation to a successful, solution-centric approach that includes sales, marketing, communication, and a problem-solving mentality.